Gelatin From Cartilage of Siberian Sturgeon (Acipenser baerii): Preparation, Characterization, and Protective Function on Ultraviolet-A-Injured Human Skin Fibroblasts - Zhang, Zhe; Wang, Yu-Mei; Qiu, Yi-Ting; Chi, Chang-Feng; Luo, Hong-Yu; Wang, Bin (Frontiers in Marine Science, 2022)
For full use of the by-products during Siberian sturgeon (Acipenser baerii) processing, gelatin was extracted from the cartilages using the hot water method, and its physico-chemical properties and protective function on ultraviolet-A injured human skin fibroblasts (HFSBs) were measured. Using single-factor and orthogonal experiments, the conditions for extracting gelatin from Siberian sturgeon cartilage were optimized as extraction time of 7 h, pH 9, material-to-liquid ratio (g/ml) of 1:5, and temperature of 45°C. The prepared gelatin (TCG) with a yield of 28.8 ± 1.53% had Gly (307 residues/1,000 residues) as the major amino acid and contained a lower amount (214 residues/1,000 residues) of imino acids than that (227 residues/1,000 residues) of pigskin gelatin (PSG). Sodium dodecyl sulfate–polyacrylamide gel electrophoresis (SDS-PAGE), ultraviolet spectrum, and infrared spectroscopy analysis indicated that TCG had the main spectral characteristics of fish gelatin and contained α chains (α1 and α2 chains) and β chain of type I collagen, but its structural stability was lower than that of PSG due to its low content of imino acids, which induced the smaller molecular bands observed in the SDS-PAGE pattern. TCG exhibited lower water content, gel strength, emulsion stability index, foam capacity, foam stability, and water-holding capacity but higher ash content, transmittance, emulsion activity index, and fat-binding capacity (P < 0.05). Moreover, TCG could significantly protect HFSBs against ultraviolet-A injury by enhancing the activity of superoxide dismutase, catalase, and glutathione peroxidase to scavenge excess reactive oxygen species and decrease the content of malondialdehyde. Therefore, gelatin from Siberian sturgeon cartilages could act as promising candidates when applied in health-promoting products against ultraviolet-A injury.